Investigation of CryptoPS LFA-positive sera in patients at risk of cryptococcosis. (23rd September 2022) - Aissaoui, Nesrine; Benhadid-Brahmi, Yasmine; Sturny-Leclère, Aude; Hamane, Samia; Payet, Eliane; Bonnal, Christine; Munier, Anne-Lise; Denis, Blandine; Alanio, Alexandre
Abstract: Cryptococcal antigen (CrAg) is a capsule polysaccharide antigen that can be detected in the fluids of patients with cryptococcal infections. Cryptococcal Antigen Latex Agglutination System (CALAS), enzyme-linked immunosorbent assays (EIA), and lateral flow assay (LFA) are the main methods available. Two main commercial LFA kits are available: CryptoPS (Biosynex, Illkirch Graffenstaden, France) and CrAg LFA (IMMY, Inc. USA). In our lab, we prospectively used CryptoPS as a screening tool in serum for confirmed positive results with CALAS. We investigated the rigor of the CryptoPS test in serum in a multicentric evaluation over 3 years. To improve the specificity of CryptoPS in serum, we additionally implemented and evaluated a pretreatment protocol before CryptoPS testing. A total of 43 serum samples collected from 43 patients were investigated. We found that the CryptoPS assay is hampered by a high rate of false-positive results in serum with a high rate of CryptoPS-positive but CrAg LFA-negative and CALAS-negative sera in patients with no proof of Cryptococcus infection ( n = 29). Using a simple pretreatment procedure (5 min incubation at 100°C and centrifugation) we were able to reverse false-positive results, suggesting that there could be interferent material present in the serum. Pretreatment also impacted the CryptoPS results (negative result) in two patients with the cryptococcal disease, one with isolated antigenemia and one with cryptococcal meningitis. Comparing the titers obtained with CALAS and CrAg LFA, we noticed that the titer obtained with CrAg LFA was almost 10-fold higher than those with CALAS. This study showed that Biosynex CryptoPS in serum could give false-positive results even in the absence of cryptococcal disease. These could be reduced by applying an easy pretreatment procedure to the serum before testing, with little but existing impact on the sensitivity. Lay Summary: Lateral flow assays are useful to detect the cryptococcal antigen in human fluids. We investigated CryptoPS-positive results and observed that true false-positive results occurred. The false-positive results can be reduced by applying an easy pretreatment procedure.